Publishing Patterns in BRIC Countries: A Network Analysis - Miguel R. Guevara; Marcelo Mendoza (Publications, 2016)
How similar are the publishing patterns of among Brazil, Russia, India and China (BRIC countries) in comparison with other countries? This is a question that we addressed by using networks as a tool to analyze the structure of similarities and disparities between countries. We analyzed the number of publications from 2006 to 2015 that are reported by SCImago Journal and Country Rank. With this information, we created a network in order to find the closest countries to BRIC ones, and also to find communities of similar countries favoring data analysis. We found that Brazil, China and Russia are not that close to the core cluster of countries that are more diversified. In opposition, India is closer to a community of countries that are more diverse in terms of publishing patterns. Furthermore, we found that, for different network topologies, Brazil acts as a bridge to connect developing countries and that Russia practices patterns that tend to isolate it from most of the countries.